Journal Eksistensi Pembelajaran Bahasa Sanskerta di Sekolah Menengah Atas Utama Widya Pasraman Astika Dharma: Eksistensi Pembelajaran Bahasa Sanskerta di Sekolah Menengah Atas Utama Widya Pasraman Astika Dharma - Ernayanti, Ni Wayan; Winanti, Ni Putu; Suyeni, Ni Made (UPADHYAYA: JURNAL PENELITIAN PENDIDIKAN, 2024)
Abstrack    Sanskrit is the language used in the Vedas so it is very important for Hindus to learn, but Sanskrit is not widely known by Hindus. A phenomenon at Widya Pasraman Astika Dharma Senior High School is learning Sanskrit which is very interesting to study. The purpose of this study was to find out the reasons for the Widya Pasraman Astika Dharma Main Senior High School making Sanskrit as one of the subjects, knowing the learning patterns and the existence of Sanskrit learning in Widya Pasraman Astika Dharma Main High School. Data collection methods used are: observation, interviews, literature studies, and documentation. The data that has been collected was analyzed using a qualitative descriptive method. Based on the results of this study, it shows that Sanskrit is a subject at the Widya Pasraman Astika Dharma Main High School because the Minister of Religion has determined Sanskrit to be one of the Hindu religious subjects at the Widya Pasraman Main school level, and is supported by the presence of adequate teachers and infrastructure. The pattern of learning Sanskrit includes material on the history of the development of the Sanskrit language, Devanāgarī letters, grammar and slokas, learning methods using conversational methods, discussion and dharmagita methods, power point learning media and Mastery Learning learning models. Learning Sanskrit at the Widya Pasraman Main Senior High School exists and has a positive impact on changes in student behavior. Students are able to understand the use of sentences in Sanskrit, are able to think, say, and behave properly, as well as increase students' Sraddha and Bhakti.